Analysis and Simulation of High Voltage Gain of Modified Sepic Converters - Rajakumari R, Felshiya; Deshpande, Dr.Mrunal (PREPARE@u® | IEI Conferences, 2021)
In this work, converter investigation takes place to achieve high voltage gain. In recent times, high step up boost converter is employed to improve the voltage gain with Sepic converter by diminish the number of components. The existing work deals with the boost converter to achieve the high voltage gain but it leads to the drawback due to the high switching losses and high switching stresses. So the proposed topology work deals with the combination of boost converter and sepic converter, i.e., modified sepic converter it takes place in the single switch device and with a coupled inductor so it is easy to achieve a high gain voltage. The proposed structure is modular and it also limited to the duty range value 0.8. The performance parameters ripple techniques is find out for the proposed converter. The proposed work deals with continuous mode operation. Simulation results are carried out in MATLAB/SIMULINK.